Analisis Kode Etik Guru Dalam Menjalankan Profesi dan Problematikanya Di Era Society 5.0 - Mega Aulia; Adelia Ramadhani; Juliyanda; Rully Hidayatullah; Hadeli (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2025)
This research aims to analyze the application of the Teacher Code of Ethics in the education profession in the era of Society 5.0 (Harly et al 2025). In addition, this research also identifies various problems that arise along with technological advances. The Teacher Code of Ethics acts as a moral and professional guideline that regulates the behavior and responsibilities of teachers in carrying out their duties, with the aim of maintaining the dignity of the profession and creating a fair and dignified educational process (Suciyati et al 2025). However, amidst the development of Society 5.0, which is characterized by the integration of advanced technologies such as artificial intelligence (AI), big data, and digital connectivity, the implementation of this code of ethics faces significant challenges (Ifadhila et al 2024). The digital divide between teachers in urban and rural areas, variations in technological skills, and low understanding of digital ethics are factors that affect the implementation of the code.